STRATEGI GERILYA DALAM MENGGUGAH KESADARAN MASYARAKAT ATAS INSTRUMEN INVESTASI PADA PRODUK PASAR MODAL SYARIAH KHUSUSNYA REKSA DANA SYARIAH - Anugrah Natalina, Sri (Istithmar, 2018)
Indonesia's financial market is a potential target, because there are still many Indonesian who in their investment patterns do not reflect the diversity and choice of modern investment instruments. This becomes a "homework" to be completed. The maximum absorption of investment funds from Indonesian society that is still conventional can "excite" the capital market again. Shariah mutual funds have a special appeal compared to other types of mutual funds. Shariah mutual funds are currently not limited to Muslims because the general public, who have seen the benefits of investment based on the selection of sector and company with certain criteria, are more promising and minimize risk. Investment portfolio management works based on the framework for investment management which covers the process of planning, implementation, evaluation and adjustment. In mutual funds, investment managers are responsible for investment activities, which include analysis and selection of investment types, and taking necessary actions for the benefit of investors. If there is a problem in the future and the investor wants to change the form of his investment, then he can do the resale of the Shariah mutual fund shares to the mutual fund company where he invests. The Shariah Supervisory Board oversees the transactions of Mutual Fund issuing companies, because the halal returns / funds obtained through mutual funds depend heavily on investment activities carried out by investment managers. The advantage of investing in Shari'ah mutual funds is that it can be done in retail so that the initial investment can be adjusted to financial capability and its value is small. Other benefits include the relatively higher yield of deposits and tax free, as well as the existence of routine audits and supervision by the Shariah Supervisory Board (DPS).